An exploratory study of pre-service teachers' computational thinking and programming skills - Umutlu, Duygu (Journal of research on technology in education, 2022)
This qualitative case study was designed to explore pre-service teachers' computational thinking and programming skills in an educational technology course in which block-based programming was introduced in a teacher education program. 12 teacher candidates from different subject areas participated in the study. The findings show that participants' views about computational thinking along with their programming skills evolved over the semester. They were mainly involved pattern recognition, debugging and trial-and-error to program coding tasks. They also used simple codes within a context and implemented remixing to solve complex problems. It can be concluded that well-designed educational technology courses for programming might be effective even for pre-service teachers who are novice coders. Further research and implications for teacher education curricula are also discussed in the paper.